2015
DOI: 10.1038/srep09569
|View full text |Cite
|
Sign up to set email alerts
|

Designing Dual-functionalized Gels for Self-reconfiguration and Autonomous Motion

Abstract: Human motion is enabled by the concerted expansion and contraction of interconnected muscles that are powered by inherent biochemical reactions. One of the challenges in the field of biomimicry is eliciting this form of motion from purely synthetic materials, which typically do not generate internalized reactions to drive mechanical action. Moreover, for practical applications, this bio-inspired motion must be readily controllable. Herein, we develop a computational model to design a new class of polymer gels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…While a few examples showed enzyme switches to achieve chemically driven out‐of‐equilibrium behavior on visible scale, these systems did not yield any macroscopic motion [36,37] . The only chemically driven out‐of‐equilibrium system that generated macroscopic motion relies on the Belousov‐Zhabotinsky (BZ) oscillating reaction, limiting the scope for general applications [38,39] . Notably, He et al .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…While a few examples showed enzyme switches to achieve chemically driven out‐of‐equilibrium behavior on visible scale, these systems did not yield any macroscopic motion [36,37] . The only chemically driven out‐of‐equilibrium system that generated macroscopic motion relies on the Belousov‐Zhabotinsky (BZ) oscillating reaction, limiting the scope for general applications [38,39] . Notably, He et al .…”
Section: Figurementioning
confidence: 99%
“…[36,37] The only chemically driven out-of-equilibrium system that generated macroscopic motion relies on the Belousov-Zhabotinsky (BZ) oscillating reaction, limiting the scope for general applications. [38,39] Notably, He et al reported a self-regulating 2dimensional surface that elegantly combines a bi-phasic microfluidic device with an exothermic reaction; [30] nevertheless, 3dimensional macroscopic actuation was not possible for this system.…”
mentioning
confidence: 99%
“…Methylcellulose (teal) is used as a crowding agent to promote crosslinking of neighboring microtubules (Sasaki et al, ). (j) Synthetic network: Polymer gels with spirobenzopyran chromophores and ruthenium catalysts (blue and green, inset) drive the Belousov‐Zhabotinsky reaction leading to oscillatory motility in the active material (Kuksenok & Balazs, ). (k) Synthetic cluster: Pluroinic F127‐DA micelles, which form in the presence of the activated photo‐initiator Irgacure 2,959 (purple), crosslink to form potentially functional clusters (X. Liu et al, ).…”
Section: Gliding Assays: the First Motile Engineered Biological Micromentioning
confidence: 99%
“…The BZ reaction typically runs at a pH of 0–2! Nonetheless, the ability of these systems not only to move but also to change shape suggests that the effort is worthwhile. Light is a powerful, versatile, and relatively noninvasive tool, and we are just at the beginning of learning how to exploit it to control chemically driven locomotion.…”
Section: Future Directionsmentioning
confidence: 99%